Management of Nitrogen Through the Use of Leaf Color Chart (LCC) and Soil Plant Analysis Development (SPAD) or Chlorophyll Meter in Rice Under Irrigated Ecosystem. (2004) - Maiti, Debtanu; Das, D. K.; Karak, Tanmoy; Banerjee, Mahua
Abstract : A field experiment was conducted in a farmers field in the district of Nadia, West Bengal, India to study the management of N through leaf color chart (LCC) and soil plant analysis development (SPAD) or chlorophyll meter in rice (cv. IET-4094) during the Kharif (wet season) of 20012002 and 20022003 by taking the treatment combinations based on different levels of N at fixed schedule and through LCC and SPAD. The experimental soil (015 cm) had pH 7.33; organic C 0.43%; available N 408.70 kg ha −1 ; available P 6.92 kg ha −1 ; and available K 66.31 kg ha −1 . The results of LCC and SPAD or chlorophyll meter for the N management in rice show that values of both LCC and SPAD significantly increased with an increasing level of N. The mean values of LCC and SPAD varied from 3.195.31 and 27.3639.26, respectively, in rice. The results show that the amount of N can be saved as 2042.5 and 27.547.5 kg N ha −1 through the use of LCC and SPAD in rice over the fixed-timing N treatment T7 where 150 kg N ha −1 was applied in three (3) splits without reduction in the yield. The SPAD- and LCC-treated N plot showed higher N-use efficiency over fixed-scheduling N treatment in rice. The results further show that SPAD value of 37 and LCC value of 5 have been proved to be superior treatments over SPAD (35) and LCC (4) for the best management of N in rice in an Inceptisol.